INCREASING TEACHERS' CAPABILITIES IN INTERACTIVE VIDEO LEARNING DURING THE COVID-19 PANDEMIC USING WHATSAPP THROUGH GROUP GUIDANCE AT SD NEGERI TRAYU KAPANEWON SAMIGALUH - Asih Asih (International Journal of Chemistry Education Research, 2021)
The Covid-19 pandemic has had an impact on the education sector, especially elementary school education. Online learning is of course carried out with various platforms and media to support teaching and learning activities. This study aims to review the use of interactive videos with WhatsApp, the learning used in learning for students at the elementary school level, and determine the ability of teachers and the content of online learning videos used as learning media at SD Negeri Trayu Kapanewon Samigaluh during the COVID-19 pandemic. This research method uses qualitative descriptive research, namely describing the use of learning media with interactive video with WhatsApp used and its application in SD Negeri Trayu Kapanewon Samigaluh. Data collection techniques using observation, interviews, and documentation. The results of this study are media using WhatsApp as online learning in the form of interactive videos. The stages of making online learning videos are in the form of planning, procurement, storage, and evaluation in the learning media, and also explaining the contents of online learning videos, so it can be concluded that online learning videos contain the results of teacher videos in classroom teaching activities that are made by the teacher in turns. then shared via Whatsapp media. With this media, teachers are more confident and students become more confident and it seems as if they are studying in a normal school. So that students and parents understand the activities or material presented by the teacher in the video.